The Combined Use of Simulation and Friction and Wear Experiments in the Research of Green Lubricants - Xuan Yin; Dingyao Zhang; Haosheng Pang; Bing Zhang; Dameng Liu (Lubricants)
During the operation of mechanical equipment, due to the intense friction among raw material or filler particles, there is conspicuous wear on the contact surfaces of components. Using green lubricants assumes a crucial role in mitigating the friction and wear, enhancing the equipment’s service life and the production’s reliability. This review centers on investigating the wear mechanism of green lubricants and undertakes a comprehensive summary and in-depth analysis of the research approach, integrating numerical simulation and friction and wear experiments. Moreover, the construction of the friction and wear testing machine and the intelligence of the testing system were probed, offering valuable design theories and research schemes for the development of effective anti-wear green lubricants.